On Complexity of Confluence and Church-Rosser Proofs - Arnold Beckmann (Mathematical Foundations of Computer Science (MFCS), 2024)
In this paper, we investigate confluence and the Church-Rosser property - two well-studied properties of rewriting and the λ-calculus - from the viewpoint of proof complexity. With respect to confluence, and focusing on orthogonal term rewrite systems, our main contribution is that the size, measured in number of symbols, of the smallest rewrite proof is polynomial in the size of the peak. For the Church-Rosser property we obtain exponential lower bounds for the size of the join in the size of the equality proof. Finally, we study the complexity of proving confluence in the context of the λ-calculus. Here, we establish an exponential (worst-case) lower bound of the size of the join in the size of the peak.